Pendampingan Menggunakan Pendekatan Akuntansi untuk Meningkatkan Efisiensi dan Kualitas Pembelajaran Bacaan Al-Qur'an di Taman Pendidikan Al-Qur'an Khoirul Huda - Adhi Riza Aulia, Adhi Riza; Wafi Najmi Naufal Athallah; Hendri Hermawan Adinugraha; Ade Gunawan (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2024)
The purpose of this training program is to improve the soft skills of the students facing digital era in order have a good communication by using English actively. The target of this training is X class students at SMK Matsaratul Huda. The training consist of 3 stages, namely; at the presentation stage, discussion stage, and practice stage. The main purpose of this training is to make the participants mastering theory and practice of public speaking. The results shown that the participants have never received special public speaking training, especially using English. At the first time they felt insecure and thought they would not be able to do it. However, after seeing the example given by the facilitator in the training, the participants began to be challenged to try to practice speaking by using English. The results of this activity shown that the students have the potential to master a good communication, they can increase pronouncing vocabulary in the right form, and also, they can arranged grammar correctly. Most of participants then felt enthusiastic to try to practice the strategies that had been conveyed by the presenters, especially in mastering speaking English.